Fake Love or True Love? Sacrificial Love as the Essence of Love of Work Phenomenon in Indonesian Elite Forces - Aulia Aulia; Fathul Himam; Rahmat Hidayat; Arief Budiarto (Journal of Educational, Health and Community Psychology, 2019)
AbstractÂ The purpose of this study was to explore the essence of the love of work phenomenon based on the experience of soldiers in elite forces. This study used a qualitative approach with a grounded phenomenology perspective. The strategy used in this study was maximal variation sampling, namely soldiers in elite forces of the Army (Kopassus), Navy (Kopaska), and Air Force (Korpaskhas), who ranked Enlisted, Non-Commissioned Officer, and Officer and were willing to participate in the study. Data collection was done through in-depth interviews. The data obtained were then analyzed using the MaxQda 12 program. The results of the study show that the essence of love of work is sacrifice. Love of work is constructed as a relationship of positive emotions between workers and their work that occurs reciprocally, is strong and has a deep meaning that is marked by the existence of sincere sacrifices when carrying out their work. The love that elite members have for their work is characterized by zeal, closeness, loyalty, and heartiness in work.Â Keywords: love of work, sacrifice, elite forces.Â